Effect of Temperature, Pressure, and Reaction Time on Hydrogenation of Hexadecanoic Acid to 1-Hexadecanol Using a Ru-Sn(3.0)/C Catalyst - Nor Ain; Rodiansono Rodiansono; Kamilia Mustikasari (Jurnal Kimia Sains dan Aplikasi, 2019)
Effect of temperature, initial H2 pressure, and reaction time on the selective hydrogenation of hexadecanoate acid to 1-hexadecanol over bimetallic ruthenium-tin supported on carbon (denoted as Ru-Sn(3.0)/C; 3.0 is molar ratio Ru/Sn) has been systematically investigated. Ru-Sn(3.0)/C catalyst was synthesized using a simple hydrothermal method at temperature of 150oC for 24 h followed by reduction with hydrogen at at 400oC and 500°C for 1.5 h. The XRD patterns of reduced Ru-Sn(3.0)/C showed a series diffraction peaks of bimetallic alloy Ru3Sn7 at 2θ = 30.0°; 35.0°; and 41.3° which are recognized as (310), (321), and (411) reflection planes present. The N2-adsorpsion/desorption profiles confirmed that the catalyst structure was microporous and mesoporous sizes with specific surface area (SBET) of 207 m2/g, pore volume (VpBJH) 0.1015 cm3/g, and pore diameter (dpBJH) 1,21 nm. NH3-TPD profile shows that the desorption temperature of 157.1°C was a weak acidity (Bronsted acid site) with amount of acid sites was 0.117 mmol/g. Meanwhile, the desorption temperature of 660.3°C was a strong acidity (Lewis acid site) with amount of acid sites was 0.826 mmol/g. The highest conversion of hexadecanoic acid (86.24%) was achieved at reaction temperature180°C, initial H2 pressure of 5.0 MPa, a reaction time of 6 h in ethanol solvent and afforded yield of hexadecane (0.15%), 1-hexadecanol (4.27%), and ethyl hexadecanoate (81.82%). At reaction temperature of 150°C, H2 of 3.0 MPa, and a reaction time of 18 h, 73.27% of hexadecanoic acid was converted to 1-hexadecanol (0.24%) and ethyl hexadecanoate (73,03%).